Distribution and molecular characterization of Malassezia species isolated from students with pityriasis versicolor in Haiphong City, 2016 - 2017 - Hien, Vo Thi Thanh; Anh, Do Ngoc (Tạp chí Y học Dự phòng, 2021)
This research aims to fnd out the Malassezia species in secondary school students with pityriasis versicolor in Hai Phong City, Vietnam. A total of 110 Malassezia fungal strains from 109 students were isolated from pityriasis versicolor patients in four secondary schools in Hai Phong City from August 2016 to December 2017. These samples were cultured on mDixon agar medium containing antibiotic at 32oC for 7 days. All Malassezia isolates were correctly identifed to the species level by CHROMagarTM Malassezia medium and molecular tools (PCR-RFLP and D1/D2 region sequencing). The results showed that M. furfur and M. japonica are two species that caused pityriasis versicolor at the rate of 96.4% and 3.6%, respectively. Most of these Malassezia isolates were isolated in the back, face, and neck. M. furfur was discovered in both areas, while M. japonica was found only in the urban area. M. furfur and M. japonica were two Malassezia species causing pityriasis versicolor in secondary school students in Hai Phong City of Northern Vietnam, in which M. furfur was more common than M. japonica, whereas other Malassezia species were not detected.